IMPLEMENTASI LAYANAN KONSELING KELOMPOK DALAM UPAYA MENINGKATKAN KONSENTRASI BELAJAR SISWA - Tita Astria (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This study discusses increasing student learning, the results of observations show that many students of MTs Negeri 1 Pangandaran have problems in learning that increase student learning. To overcome this problem, it is necessary to provide services that can accommodate the interests of a number of these students together such as group counseling services. By implementing group counseling services, it is expected to increase students' learning for achievement that is free from improvement. Adding group counseling services used here is an activity of giving assistance with groups or problems related to personal and confidential in groups intended for personal development, discussion and solving personal problems needed by each group member. This research is a classroom action research conducted in 2 cycles in students of class IX-A in the year of 2017/2018 which tests 35 students. The results of the study (1) through the implementation of group counseling services can improve learning for achievement that is free from the initial conditions 57.1% into the education cycle level of 34.5% in class IX students. A. MTs Negeri 1 Pangandaran. So with this group counseling service, the rate of increase in students is increasing. (2) through learning groups improve learning efficiency for achievement which frees from understanding in class IX students. A. MTs 1 Pangandaran Academic Year 2017/2018.